2017
DOI: 10.1016/j.legalmed.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Estimating normal lung weight measurement using postmortem CT in forensic cases

Abstract: The well aerated lung weight was 284.9 ± 14.8 g in right lung and 249.3 ± 12.9 g in left lung, and the postmortem CT could estimate the lung weight with high correlation coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…Average lung weights [3, 9, 21-26] were plotted on MATLAB (MathWorks, Natick, MA, USA) and Microsoft Excel (Microsoft Corporation, Redmond, WA, USA). A one-way Analysis of Variance (ANOVA) coupled with a post-hoc analysis was performed using a Tukey Honestly Significant Difference (HSD) test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Average lung weights [3, 9, 21-26] were plotted on MATLAB (MathWorks, Natick, MA, USA) and Microsoft Excel (Microsoft Corporation, Redmond, WA, USA). A one-way Analysis of Variance (ANOVA) coupled with a post-hoc analysis was performed using a Tukey Honestly Significant Difference (HSD) test.…”
Section: Resultsmentioning
confidence: 99%
“…The goal of an autopsy is to discover the cause of death (COD) using a macro/microscopic investigation. Because lung weight is often affected by the cause of death and the last breath occurs very near if not at death, the evaluation of the lungs is one of the starting points of any COD investigation [3] . A comprehensive search was performed to systematically review all reported autopsy findings in COVID-19 patients with respect to lung weights and histologic findings.…”
mentioning
confidence: 99%
“…This might partially explain why unilateral right lung pathology is often clinically more severe than unilateral left, such as in right-sided CDH which has been associated with greater long-term morbidity ( 14 ), although clearly other factors might also play a role such as that the liver, which is herniating in right-sided CDH, is a non-compressible organ. In children and young adults, the volume of the right lung has been reported as 1.12 times larger than the volume of the left lung ( 15 ) and the weight as 1.14 times larger ( 16 ) but the projection of a three-dimensional structure to a two-dimensional radiograph might explain this discrepancy.…”
Section: Discussionmentioning
confidence: 98%
“…The CAD curve displayed a bimodal distribution after a rapid rise, but only one peak was found in drowning. In a previous report, the CT value range, from −1 000 to −700 HU, was used to assess the normal aerated lung [ 20 ]. Compared with the normal aerated lung, the lung CT value increased both in drowning and control group.…”
Section: Discussionmentioning
confidence: 99%